Ocular toxocariasis. A case presentation - Mariela Julia Curbelo Gómez; Bárbara Teresa Ríos Araujo; María Adela LLull Tombo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
A clinical case on ocular toxocariasis is presented. The clinical manifestations were pain and red eye in a four year-old child. A prior acute uveitis in the LE was found in the physical ocular exam. Vitrea band that was out of the superior edge of papila and a marginal granuloma were found in the eyes fundus. The patient was admitted and treated with oral corticoids and oral antihelmintics